How much traffic stress can cyclists endure?. Issue 4 (December 2022) - Halefom, Tmnit H.; Pullar, David; Pojani, Dorina; Asamoah, Ernest Frimpong
Highlights: One of few studies to asses traffic stress among cyclists. Applies a novel index called Average Traffic Stress (ATS). A study based on GPS-tracked cycling trips ('big data') rather than population surveys. Abstract: Bicycles are a desirable but underutilised form of travel in many cities. A main barrier to a large uptake of cycling for travel is traffic safety. To assess how much traffic stress cyclists can endure and how this stress affects route choices, we have developed an index called Average Traffic Stress (ATS). This index aggregates several measurable characteristics, but the key ones are the trip distance and a road segment's Level of Traffic Stress (LTS). Using Brisbane, Australia, as a case study, we analyse 3, 304 GPS-tracked cycling trips and apply a multilevel regression model to link ATS to the individual characteristics of cyclists, as well as environmental characteristics. We find that younger male cyclists who make longer trips at higher trip speeds experience higherATS. Recreational trips produce less ATS. Flat topography, a disconnected street network, and a lack of cycling infrastructure are associated with higher ATS. Cyclists intuitively select routes with less car traffic and/or better cycling infrastructure to achieve the lowest level of ATS (rather than selection routes with the shortest distance or the flattest topography).